2021
DOI: 10.1155/2021/8894636
|View full text |Cite
|
Sign up to set email alerts
|

Do Novice Runners Show Greater Changes in Biomechanical Parameters?

Abstract: Purpose. Examining and understanding the biomechanics of novice runners and experienced runners can further improve our knowledge within the field of running mechanics and running injuries. The purpose of this study was to classify the differences in lower limb biomechanics during a 3.3 m/s running task among both experienced runners and novice runners. Method. Twenty-four participants (12 experienced runners and 12 novice runners) ran at 3.3 m/s across a force plate; kinematics and kinetics data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Increased internal and external rotation and internal abduction of the hip joints are associated with patellofemoral pain and iliotibial tract syndrome [38,39]. Our results for the hip sagittal plane PC2 were consistent with previous studies using traditional analysis techniques that reported greater hip flexion and hip ROM for novice runners [11]. Peak adduction and hip ROM in the frontal plane reflect in the hip frontal plane PC1.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Increased internal and external rotation and internal abduction of the hip joints are associated with patellofemoral pain and iliotibial tract syndrome [38,39]. Our results for the hip sagittal plane PC2 were consistent with previous studies using traditional analysis techniques that reported greater hip flexion and hip ROM for novice runners [11]. Peak adduction and hip ROM in the frontal plane reflect in the hip frontal plane PC1.…”
Section: Discussionsupporting
confidence: 90%
“…The hip joint is a complex structure, and greater hip flexion and hip ROM for novice runners has been observed. However, the ankle and knee did not differ between novice and experienced runners' kinematics data [11].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Joint angles, joint moments, joint power, and joint work were normalized to the gait cycle over 101-time points. Ankle, knee and hip angles were calculated using Cardan angles in the sagittal plane (positiveflexion/dorsiflexion; negative-extension/plantarflexion) (Quan et al, 2021).…”
Section: Sagittal Plane Kinematicsmentioning
confidence: 99%